Titelbild: Der starre Kern und die flexible Oberfläche von Amyloidfibrillen – Magic‐Angle‐Spinning NMR Spektroskopie von aromatischen Resten (Angew. Chem. 19/2023). (30th March 2023) - Becker, Lea Marie; Berbon, Mélanie; Vallet, Alicia; Grelard, Axelle; Morvan, Estelle; Bardiaux, Benjamin; Lichtenecker, Roman; Ernst, Matthias; Loquet, Antoine; Schanda, Paul
Abstract : Rock‐solid amyloid? . Aromatic residues in the core of the amyloid fibrils HELLF and HET‐s show no sign of ring flips suggesting a rigid core that does not undergo "breathing motions". Aromatic residues facing outside on the other hand are highly flexible and show ring flips on various timescales. These conclusions could be drawn from dynamics measurements by solid‐state MAS NMR in combination with specific labeling of phenylalanines and tyrosines as Paul Schanda et al. describe in their Research Article (e202219314 ).